Sugar-Sweetened Beverage Consumption and Risks of Obesity and Hypertension in Chinese Children and Adolescents: A National Cross-Sectional Analysis - Zhao-Huan Gui (Nutrients, 2017)
We investigated the consumption of sugar-sweetened beverage (SSB) and its association with obesity and hypertension in a national sample of children and adolescents in China, where many low- and middle-income families live. Data were obtained from a 2014 national intervention program against obesity in Chinese children and adolescents aged 6–17 years. Height, weight, waist circumference, and blood pressure were measured. Information of SSB consumption, socioeconomic status, dietary intake, screen time, and physical activity were self-reported. Multivariate logistic regression was used to assess the association of SSB consumption with obesity and hypertension. A total of 66.6% of the 53,151 participants reported consuming SSB. The per capita and per consumer SSB intake were 2.84 ± 5.26 servings/week and 4.26 ± 5.96 servings/week, respectively. Boys, older children, and adolescents, and individuals with long screen time or high physical activity or low parental education level were more likely to consume SSB. Participants who were high SSB consumers had a higher odds ratio (1.133, 95% CI: 1.054–1.217) than non-consumers for having abdominal obesity after adjustment for age, sex, residence, socioeconomic status, diet, screen time, and physical activity. However, SSB consumption was not associated with general obesity or hypertension in children and adolescents. In conclusion, more than half of the children and adolescents in China consumed SSB, which was independently related to a high risk of abdominal obesity. The results of this study indicated that SSB reduction strategies and policies may be useful in preventing obesity among Chinese children and adolescents.